2022
DOI: 10.3389/fendo.2022.838858
|View full text |Cite
|
Sign up to set email alerts
|

What Does Androgen Receptor Signaling Pathway in Sertoli Cells During Normal Spermatogenesis Tell Us?

Abstract: Androgen receptor signaling pathway is necessary to complete spermatogenesis in testes. Difference between androgen binding location in Sertoli cell classifies androgen receptor signaling pathway into classical signaling pathway and non-classical signaling pathway. As the only somatic cell type in seminiferous tubule, Sertoli cells are under androgen receptor signaling pathway regulation via androgen receptor located in cytoplasm and plasma membrane. Androgen receptor signaling pathway is able to regulate biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 188 publications
(224 reference statements)
0
24
0
Order By: Relevance
“…30 As a result of studies from various animal models, it has been determined that the LH-testosterone signaling pathway has a critical role in the initiation and maintenance of spermatogenesis. 31 Again, LH/testosterone and FSH are very important for testicular function and spermatogenesis. 32 It has been determined that some chemicals affect these hormones, which are so important for testicular functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 As a result of studies from various animal models, it has been determined that the LH-testosterone signaling pathway has a critical role in the initiation and maintenance of spermatogenesis. 31 Again, LH/testosterone and FSH are very important for testicular function and spermatogenesis. 32 It has been determined that some chemicals affect these hormones, which are so important for testicular functions.…”
Section: Discussionmentioning
confidence: 99%
“…The critical hormone that maintains spermatogenesis in the testis is testosterone 30 . As a result of studies from various animal models, it has been determined that the LH‐testosterone signaling pathway has a critical role in the initiation and maintenance of spermatogenesis 31 . Again, LH/testosterone and FSH are very important for testicular function and spermatogenesis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…And mature SCs no longer have the ability to proliferate in vivo . Importantly, adult mouse and human Sertoli cells can resume proliferation in vitro , suggesting that they could be proliferating cells at rest rather than terminally differentiating cells ( 35 , 36 ). Our study also demonstrated that Sertoli cells from sexually mature yaks restored their proliferative capacity in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…To investigate if Sertoli cells in type A tubules are mature as their nuclei morphology and localization along the basement membrane in the tubules suggest, we stained with antibodies against three Sertoli cell maturity markers, the androgen receptor (AR) (Sharpe et al, 2003;Wang et al, 2022), Clusterin (CLU, also known as SGP-2), which is secreted from mature Sertoli cells (Sharpe et al, 2003;Sylvester et al, 1984), and defensin beta 119 (DEFB119), a newly identified marker (Mahyari et al, 2023;Zhao et al, 2020). All three markers were highly expressed in type A Sertoli cells which was in contrast to type B Sertoli cells showing low expression levels (Fig.…”
Section: Micro-mosaicism Of Type a And B Sertoli Cellsmentioning
confidence: 99%